Influência de fatores históricos e ecológicos sobre a estruturação de uma taxocenose de lagartos em uma área de caatinga hipoxerófila do Brasil - Vilanova-Júnior, José Leilton (2020)
Several elements can influence the dynamics within a taxocenosis, whether they are of a stochastic or deterministic nature. From a deterministic point of view, the structuring may be the result of the performance of contemporary factors and, also, a reflection of the differences in the evolutionary history between the lineages that compose it. Thus, the objective of this project was to analyze the spatial and trophic structure of a lizard taxocenosis in Serra dos Macacos, Tobias Barreto, Sergipe and its relationship with historical and ecological factors. The data were taken between the months of March and September 2019, in a total of four campaigns lasting 14 days each. The lizards were captured using pitfalls and glue traps and active search. For all the individuals observed and / or collected, information on the occupied substrates was recorded and the collected specimens had their digestive tracts removed for analysis of the diet. Structural characteristics of the microhabitats around the pitfalls were measured and related to the abundance of the captured species. We recorded 16 species of lizards, belonging to 10 families. The most abundant species for the study area were Ameivula ocellifera (14.72%), Tropidurus hispidus (21.57%) and Tropidurus semitaeniatus (26.21%). Only A. ocellifera and Gymnodactylus geckoides showed significant relationships with some of the environmental variables measured (number of cacti and number of holes, respectively). The analysis of pseudocommunities indicated that taxocenosis is structured only in relation to the trophic niche, while the Phylogenetic Principal Component Analysis detected the influence of ecological and historical factors, the latter being the most prominent for both the food and spatial niche. The results of this study demonstrate that different lineages of lizards can respond in different ways to environmental pressures, such as competition and disponibilityof resources, denoting the importance of considering together the actions of ecological and historical factors in the interpretations on the determinants of the organization of the taxocenosis. Thus, the development of phylogenetic methods that aim to measure such effects on a local scale and their use in different communities are essential to elucidate the patterns that emerge from the complex synergy between historical and ecological factors, and so facilitate the generalization and formulation of more consistent theories on larger scales.